PENGARUH WISATA ALAM PULAU KEBAN AGUNG TERHADAP PEREKONOMIAN DI KECAMATAN SEMIDANG AJI KABUPATEN OKU - Shafera, Nurul Beauty; Pusvita, Ema; Septianita, Septianita (Universitas Galuh, 2023)
This study has directions to find out the factors that influence the natural tourism of Keban Agung Island on the economy in Semidang Aji District, OKU Regency. This research method was carried out using a quantitative method in which the research used multiple linear regression analysis. Data was obtained from business actors in Keban Agung Village. The results of this study are the factors that influence natural tourism on the economy in Keban Agung Village, namely there are four factors in cluding: the number of purchases, receipts, the number of visitors and community businesses. Of the four factors, three factors have a significant effect on the economy in Keban Agung Village, namely the number of purchases, receipts and the number of visitors, and one factor does not have a significant effect on the economy in Keban Agung Village, namely the community business factor.